Analisis CAMEL (Capital, Assets Quality, Management, Earning, Liquidity) untuk Menilai Tingkat Kesehatan Bank Perkreditan Rakyat pada PT BPR Artha Nugraha Tahun 2018–2020 - Nadiah Safa Karimah; Kukuh Harianto; Taufik Akbar (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study is meant to look at how financially strong PT. BPR Artha Nugraha, a rural bank, is. It uses the CAMEL method, which checks Capital, Assets, Management, Equity, and Liquidity, as required by Bank Indonesia's regulations, specifically BI DIR Decree Number 30/12/KEP/DIR from April 30, 1997. The research uses a descriptive quantitative approach to give a detailed look at the bank's performance. The data used comes from the bank's audited financial reports for the years 2018 to 2020, which were officially released by the Financial Services Authority (OJK). Also, the study gathered primary data by talking directly with people from the bank to learn more about the company's background, how it's run, and other important operational details.The CAMEL method was used tolcheck and look at the main performance indicators of the bank, which include capital adequacy, asset quality, management ability, profitability, and liquidity. Each of these areas was assessed using the standards set by BanklIndonesia to figure out how strong and stable the bank is overall. The study found that PT. BPR Artha Nugraha got alCAMEL score of 87.60 in 2018 and 2019, and 87.50 in 2020. These scores show that the bank kept a “healthy” condition for three straight years. So, it can be said that PT. BPR Artha Nugraha had good financial stability, strong management, and continued ability to operate well during the 2018–2020 period.